Pengaruh Pemberian Larvasida Insect Growth Regulator (IGR) Berbahan Aktif Pyriproxyfen Terhadap Perubahan Angka Bebas Jentik (ABJ) Di Kelurahan Bulusan Kota Semarang - Nur Solichah; Martini Martini; Henry Setyawan Susanto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Bulusan district is the area with endemic status of Dengue Hemorraghic Fever (DHF) for seven years and include at the big four of distrct that contribute the highest IR DHF at Semarang City. One of the vector control is the larvicide program with temephos that applied since 1980, so there is a need to rotate the larvicide to prevent the resistance of larvae Aedes spp and one of the larvicide that recommend by WHO is Insect Growth Regulator (IGR) with active ingredient is Pyriproxyfen. The aim of study is to find out the change of larvae free rate (ABJ) at Bulusan District before and after the application of IGR Pyriproxyfen larvicide and describe community acceptance of IGR Pyriproxyfen larvicide. Method of this study is quasi experiment with one group pre test and post test design with cluster random sampling. Total sample is 92 respondents that willing to interviewed and 33 respondents that willing to treatment in positive larvae container. The result of analytic statistic with Paired T Test is there is a significant differences of ABJ before and after application of IGR Pyriproxyfen larvicide at Bulusan District for a week (p<0,05) with the increase of ABJ is about 11,8%. All respondents have good acceptance of IGR Pyriproxyfen larvicide. It judged from the respondents statement that IGR Pyriproxyfen larvicide have good smell, attractive appearance and infomative, practical, and safe use. IGR larvicide with active ingredient Pyriproxyfen can be use as an alternative solution to rotate the use of temephos